Facile synthesis of fluorinated poly(arylene ether)s with pendant sulfonic acid groups for proton exchange membranes. (2nd November 2017) - Xu, Jiaqi; Lin, Qilang; Yu, Yan; Chen, Dongyang; Ye, Zhuoliang
Abstract: Linear fluorinated poly(arylene ether)s with and without pendent allyl groups (CFPAE and FPAE) were successfully polymerized from decafluorobiphenyl at room temperature. The subsequent SN2 nucleophilic substitution of the remaining F atom on CFPAE and FPAE with sodium 4-hydroxybenzenesulfonate yielded SCFPAE and SFPAEs in one simple step under mild conditions. The chemical structures of the polymers were confirmed by 1 H NMR and FT-IR. The ion exchange capacity (IEC), inherent viscosity, water uptake, swelling ratio, proton conductivity, mechanical property, thermal stability, and oxidative stability of the SFPAEs were characterized. The experimental results revealed that the IEC of the SFPAEs can be facilely controlled by the loading amount of sodium 4-hydroxybenzenesulfonate in the reaction mixture. The SFPAE-20 with an IEC of 2.0 mmol g −1 exhibited an in-plane proton conductivity of 106 mS cm −1 at 30 °C, higher than that of Nafion N212. More importantly, the SFPAEs showed significantly enhanced oxidative stabilities compared to sulfonated non-fluorinated analogs in literature. While there was still a trade-off between proton conductivity and mechanical strength as often seen for homogeneous systems, the SFPAEs were demonstrated to be promising candidates for proton exchange membranes. Highlights: Linear fluorinated poly(arylene ether)s with and without pendent allyl groups were synthesized. Sulfonate groups were incorporated via SN2 reaction with 4-hydroxybenzenesulfonate in one step. Ion exchange capacity (IEC) was tuned by the molar ratio of the reactants. SFPAE-20 with an IEC of 2.0 mmol g −1 exhibited higher proton conductivity than Nafion. Excellent oxidative stability was observed for the products because of the existence of F atom.